A reference signal based GLRT for simultaneous sensing and reception in cognitive LTE-A systems - Karunakaran, Prasanth; Gerstacker, Wolfgang (2016 IEEE Wireless Communications and Networking Conference, 2016)
We explore the application of cognitive radio (CR) principles to 3GPP LTE-A. In such a system, a cognitive radio (CR), synchronized to the macro base station (BS), exploits the spectral holes in the orthogonal frequency division multiple access (OFDMA) time-frequency grid. Spectrum sharing between different network operators and device-to-device (D2D) communications in LTE-A are presented as potential applications. Sensing is expected to play a prominent role in such systems. We focus on simultaneous sensing and reception (SSR) that can avoid the overhead in sensing before transmission (SBT) protocols. Firstly, for a flat fading channel, we develop generalized likelihood ratio tests (GLRTs) based on the demodulation reference signals (DMRSs) of transmission mode 9 in LTE-A that do not require the knowledge of signal powers, channel statistics and noise parameters. Secondly, using a polynomial fitting, we extend the algorithm to frequency-selective fading scenarios. Simulation results are presented to compare the different algorithms which indicate that good performance can be achieved for SSR with full knowledge of the DMRS

Autocorrelation Based Detection of Multicarrier Signals with Periodic Power Boosting - Karunakaran, Prasanth; Gerstacker, Wolfgang (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2018)
Given the prevalence of multicarrier waveforms in wireless systems, the sensing of such signals is of high importance for cognitive radio applications. In this work, we exploit periodic power boosting of subcarriers in multicarrier signals which is applied e.g. in LTE to improve the performance of sensing compared to state-of-the-art schemes under practical scenarios where noise uncertainties are present. First, we establish an analytical connection between the subcarrier power distribution and the autocorrelation function of a general multicarrier signal. Second, using this result, we demonstrate that periodic power boosting causes strong peaks in the magnitude of the autocorrelation function. The obtained analytical results match well with over-the-air measurement results corresponding to an orthogonal frequency division multiplexing (OFDM) signal of an LTE transmission. Here, the measurements indicate the presence of a boosting with a period of three subcarriers in the LTE signal which arises due to the cell-specific reference signals. Subsequently, a sensing algorithm exploiting the special features of the autocorrelation function resulting from periodic power boosting is developed which outperforms energy detection under realistic noise uncertainties and a state-of-the-art method that relies only on the cyclic prefi

Constant False Alarm Rate Detection of Multicarrier Signals With Periodic Power Boosting - Karunakaran, Prasanth; Gerstacker, Wolfgang (IEEE Transactions on Cognitive Communications and Networking, 2018)
Given the prevalence of multicarrier waveforms in wireless systems, the sensing of such signals is of high importance for cognitive radio applications. In this paper, we exploit periodic power boosting of subcarriers in multicarrier signals which is applied, e.g., in LTE to improve the performance of sensing compared to state-of-the-art schemes under practical scenarios where noise uncertainties are present. First, we establish an analytical connection between the subcarrier power distribution and the autocorrelation function of a general multicarrier signal. Second, using this result, we demonstrate that periodic power boosting causes strong peaks in the magnitude of the autocorrelation function. The obtained analytical results match well with over-the-air measurement results corresponding to an orthogonal frequency division multiplexing (OFDM) signal of an LTE transmission. Here, the measurements indicate the presence of a boosting with a period of three subcarriers in the LTE signal which arises due to the cell-specific reference signals. Subsequently, algorithms for both sensing before transmission and simultaneous sensing and reception exploiting the special features of the autocorrelation function resulting from periodic power boosting are developed which outperform energy detection under realistic noise uncertainties as well as several state-of-the-art methods for detecting OFDM signal

Sensing Algorithms and Protocol for Simultaneous Sensing and Reception-Based Cognitive D2D Communications in LTE-A Systems - Karunakaran, Prasanth; Gerstacker, Wolfgang (IEEE Transactions on Cognitive Communications and Networking, 2017)
We explore the application of simultaneous sensing and reception (SSR) for cognitive communication in orthogonal frequency division multiplexing (OFDM)-based wireless systems such as 3GPP LTE-A which may find application in multi-tier spectrum sharing paradigms such as the spectrum access system. In such a system, a cognitive radio (CR) synchronized to the macro base station (BS) is assumed to exploit the spectral holes in the OFDMA time-frequency grid. We analyze the impact of timing alignment in such a system and show that power control and guard bands are essential to support such an operation. Practical algorithms for SSR with the constant false alarm rate property are developed using the generalized likelihood ratio test principle to protect macro BS users occupying the same transmission resources as the CRs. Subsequently, we propose a transmission-reception protocol with SSR for bidirectional communication between two time-division duplex CRs and compare it to a protocol with only sensing before transmission (SBT). The simulation results show that the sensing overhead in traditional SBT protocols can be much reduced with the use of SSR when the BS activity in adjacent slots is highly correlate